Syphilis notifications among pregnant women in Campo Grande, state of Mato Grosso do Sul, Brazil, 2011 to 2017 - Pires,Cássia de Paula (2020)
Abstract INTRODUCTION Syphilis is a sexually transmitted infection caused by Treponema pallidum. Considering the high rates of syphilis in pregnancy and congenital syphilis reported in Brazil in the past, and their serious consequences, this study described the epidemiological and clinical profile of pregnant women with a confirmed diagnosis of syphilis in Campo Grande, in the state of Mato Grosso do Sul, Brazil, from 2011 to 2017. METHODS: This is a descriptive study, based on syphilis notifications among pregnant women reported to the Sistema de Informação de Agravos de Notificação (National System of Disease Notification of Brazil). RESULTS: Over the study period, 2,056 confirmed cases of syphilis in pregnancy were reported, resulting in a crude cumulative incidence of 144.76 cases per 1,000 live-born babies. The incidence increased from 9.97 cases per 1,000 live-born babies in 2011 to 36.10 cases per 1,000 live-born babies in 2017. It was more prevalent in women who were young, of mixed race, with low educational attainment. Over one third of women were diagnosed in the first trimester of pregnancy; therefore, they were at risk of reinfection if they or their sexual partners were inadequately treated. Furthermore, syphilis was not well classified according to its clinical stage, which led to inappropriate treatments. CONCLUSIONS: Despite efforts to reduce the incidence of syphilis, syphilis during pregnancy remains a public health problem, reflecting possible inadequacies in antenatal care, especially in vulnerable populations. It is important to include sexual partners in syphilis treatment during pregnancy to prevent reinfection.